Women's Position in Patriarchal Kinship System - Harahap, Ikhwanuddin (SCAD Independent, 2020)
Spirit of gender equalities is currently stretching amid the strong patriarchal system in North Padang Lawas District North Sumatera. In terms of education, women get the same rights as men, even in some villages, more women go to school/college than men. There is a growing slogan that is